2019
DOI: 10.1007/s00467-019-04390-9
|View full text |Cite
|
Sign up to set email alerts
|

A single-center study to evaluate the efficacy of a fetal urine peptide signature predicting postnatal renal outcome in fetuses with posterior urethral valves

Abstract: Background-Posterior urethral valves (PUV) accounts for 17% of pediatric renal failure. The management of pregnancies involving fetuses with PUV is hampered by the fact that current clinical parameters obtained from fetal ultrasound and/or fetal urine biochemistry are insufficient to predict postnatal renal function. We previously have developed a fetal urine peptide signature (12PUV) that predicted with high precision postnatal renal failure at 2 years of age in fetuses with PUV. Here we evaluated the accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…We identified and validated 12 peptides in fetal urine (FU) that predicted in utero postnatal renal survival in fetuses with developmental renal disease ( i.e. posterior urethral valves, PUV) 10 , 11 . However, in contrast to postnatal urine, sampling of FU is invasive since it is collected directly from the fetal bladder.…”
Section: Introductionmentioning
confidence: 99%
“…We identified and validated 12 peptides in fetal urine (FU) that predicted in utero postnatal renal survival in fetuses with developmental renal disease ( i.e. posterior urethral valves, PUV) 10 , 11 . However, in contrast to postnatal urine, sampling of FU is invasive since it is collected directly from the fetal bladder.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the 12 fetal urine peptides in predicting postnatal renal outcome alone was recently verified in a single center study. [ 62 ] In this study the peptide signature predicted postnatal renal outcome in postnatally confirmed PUV fetuses with an AUC of 0.94 and an in the suspected PUV cases with an AUC of 0.89. This small‐scale single center study is therefore an important premise for the recently started prospective large‐scale study, named ANTENATAL (clinicaltrials.gov NCT03116217; “multicentre vAlidatioN of a fetal urine pepTidome‐based classifiEr to predict postnatal reNAl function in posterior ureThral vALves”), aiming to validate the 12PUV signature in a much larger multicenter setting.…”
Section: Kidney Diseasementioning
confidence: 82%
“…The fetal imaging details, from the detailed ultrasound ± MRI technology, provide understanding for the extent of renal morbidity, but can create clinical variance secondary to the expertise in the LUTO diagnostic and prognostic interpretation (Table 1) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Results/interventions: Identification Of Potential Evidenced-based Protocol Elements For Development Of An Eras-luto Guidelinementioning
confidence: 99%